2020
DOI: 10.3390/cells9041008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Endocannabinoid System and Interleukin Profiles in Ovine AEC: Cannabinoid Receptors Type-1 and Type-2 as Key Effectors of Pro-Inflammatory Response

Abstract: Amniotic epithelial cells (AEC) have been proposed as promising clinical candidates for regenerative medicine therapies due to their immunomodulatory capacity. In this context, the endocannabinoid system (ECS) has been identified as mediating the immune-stem cell dialogue, even if no information on AEC is available to date. Therefore, this study was designed to assess whether ECS is involved in tuning the constitutive and lipopolysaccharide (LPS)-induced ovine AEC anti-inflammatory and pro-inflammatory interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…oAECs are able to secrete cytokines and growth factors with antiapoptotic, proangiogenic, and immune-modulatory molecules, which can alter the pro-inflammatory signals and enhance the anti-inflammatory ones, hence improving tissue regeneration [84][85][86][87][88]. Among them, it was recently demonstrated in the amniotic epithelium that a highly conserved physiological mechanism amongst species controlling the expression and releasing balance of potent anti-inflammatory and proinflammatory cytokines, such as interleukin (IL)-10, IL-4, and IL-12, under both basal and LPS-inductive conditions [54,80,89,90].…”
Section: Discussionmentioning
confidence: 99%
“…oAECs are able to secrete cytokines and growth factors with antiapoptotic, proangiogenic, and immune-modulatory molecules, which can alter the pro-inflammatory signals and enhance the anti-inflammatory ones, hence improving tissue regeneration [84][85][86][87][88]. Among them, it was recently demonstrated in the amniotic epithelium that a highly conserved physiological mechanism amongst species controlling the expression and releasing balance of potent anti-inflammatory and proinflammatory cytokines, such as interleukin (IL)-10, IL-4, and IL-12, under both basal and LPS-inductive conditions [54,80,89,90].…”
Section: Discussionmentioning
confidence: 99%
“…16 Interleukin-6 (IL-6) is an inflammatory cytokine and mediator that affects immune and nonimmuno-regulation in a variety of cell types and tissues outside of the immune system, including skeletal muscle tissue. 12,[17][18][19] IL-6 is a physiologically active cytokine that regulates inflammatory responses, skeletal muscle cell proliferation, differentiation, growth, and metabolism. 20 Recent data has shown that IL-6 is generated and released from skeletal muscle cells in the absence of inflammation and by complex signalling cascades.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Previous studies have demonstrated that skeletal muscle tissue produces IL-6. 12,19 Increasing evidence indicates that skeletal muscle is implicated in the inflammatory process via secreting cytokines. 23 The effects of cannabinoids on muscle cell cytokine expression have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“… 35 , 36 To this regard, here we demonstrate that the transient depletion of CIITA dramatically impairs the anti-inflammatory abilities of eAEC, thus demonstrating its pivotal role in the immune response of these cells. 37 …”
Section: Discussionmentioning
confidence: 99%